Jq command tutorials for Bash shell scripting, (Packt Publishing, 2022)
Be a part of the learning community to filter JSON data with ease. The Jq command is built around filters that are used to find and print only the required data from a JSON file. About This Video Highly practical and comes bundled with all the resource files including PPT files End-to-end course on Jq command with the help of live examples for an in-depth understanding Beginner's level guide to explain Jq command using Bash Shell Scripts with detailed explanation In Detail Nowadays, DevOps automation is more into REST API usage, and REST API response is JSON. So, to implement bash shell scripts using REST APIs, you must know how to parse the response of REST API (that is, parse JSON data). Jq is a program developed to filter JSON data. You can consider Jq like sed, awk, or grep program but designed specifically for filtering JSON data. Jq supports filters, conditions, operators, and other language features. While the creation and understanding of JSON data are effortless due to its human-readable format, JSON data parsing is still a very complicated task to achieve if done manually. Instead, you can use programs like Jq to parse JSON data in minutes. In this course, you will see the usage of the Jq command in Bash Shell Scripts, followed by filters and options to work with JSON objects. After that, you will look at the simple usage of the Jq command in Shell Scripts and start working with JSON arrays using the index concept. Next, you will be constructing objects and arrays with and without inputs and the usage of the -n option in Jq Command. Finally, you will study the Jq functions. By the end of this course, you will have learned and gained the requisite confidence to work with the Jq Command using Bash Shell scripting in detail. Audience This course is ideal for Bash Shell Scripting developers wanting to use Jq Command in scripts and programmers who work with JSON. IT professionals who work with JSON or anyone who works with JSON will also benefit from the course. As a prerequisite, you should have a Linux/Mac system to practice, basic knowledge of the command line, along with beginner-level knowledge of usage of pipelines and redirections. Basic knowledge of JSON data and working knowledge of any editor like vi/Vim/VS Code is recommended as well.